Utilization of Wastelands for Growing Medicinal Plants - Singh, A. K.; Banerjee, S. K.; Shukla, P. K. (Indian Forester, 2003)
Medicinal plants form an integral part of rural and urban lifestyle. But many of the species have reached the stage of ’endangered and threatened’ because of over-exploitation of forests, uncontrolled grazing and fire. In India nearly 175 million ha of land is degraded, out of which 93 million ha is lying waste. This land is not suitable for growing agricultural crops economically but can be effectively used for growing medicinal plants after proper management. In this review, species suitability for different types of wastelands, proper amendments for boosting the growth of these plants etc. have been discussed in length.